2005
DOI: 10.1007/bf02734151
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of idiopathic nephrotic syndrome

Abstract: Nephrotic syndrome (NS) is a pathological entity characterized by massive proteinuria and has diverse etiology. Although it is one of the most common renal diseases in children, the etiological factors responsible for idiopathic NS/FSGS remain largely unknown. Previous studies had implicated a variety of factors including genetic factors, although NS is generally regarded as a sporadic disease. Familial cases of NS have however been reported periodically, and both autosomal dominant and recessive forms have be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…In addition, ManNAc may have therapeutic potential for some podocytopathies. Candidate disorders include minimal change nephrosis (40), focal and segmental glomerulosclerosis (53), membranous glomerulonephritis (54), and other forms of unexplained idiopathic nephrotic syndrome (55). The Gne M712T/M712T mice unexpectedly provide a unique opportunity to study basic mechanisms and targeted therapies of podocyte injury and/or GBM splitting, for which appropriate model systems are sparse (23,38,56,57).…”
Section: Figurementioning
confidence: 99%
“…In addition, ManNAc may have therapeutic potential for some podocytopathies. Candidate disorders include minimal change nephrosis (40), focal and segmental glomerulosclerosis (53), membranous glomerulonephritis (54), and other forms of unexplained idiopathic nephrotic syndrome (55). The Gne M712T/M712T mice unexpectedly provide a unique opportunity to study basic mechanisms and targeted therapies of podocyte injury and/or GBM splitting, for which appropriate model systems are sparse (23,38,56,57).…”
Section: Figurementioning
confidence: 99%
“…Some investi gations suggested that genetic factor might play a key role in the onset of INS. [5][6][7] Angiotensinconverting enzyme (ACE) is a zinc metal lopeptidase that converts angiotensin I to angiotensin II (Ang II). 8 The ACE gene consists of either an insertion (I) allele or a deletion (D) allele forming three possible geno types: II, ID and DD.…”
Section: Introductionmentioning
confidence: 99%
“…Both syndromes are characterized by gonadal dysfunction and progressive nephropathy with FSGS, or diffuse mesangial sclerosis with onset in early childhood. In addition, isolated diffuse mesangial sclerosis patients have been shown to have WT1 mutations especially in exons 8 and 9, involving the zinc finger domain (Vats 2005).…”
Section: Genetics Of Sd-associated Glomerular Diseasementioning
confidence: 99%
“…The disease, caused by TRPC6 mutations, may be characterized by late onset (between 17 and 57 years of life) with extensive proteinuria, progression to the terminal stage of chronic kidney disease, and resistance to steroid treatment (the resistance is typical for monogenic glomerulopathies). No recurrence of the disease in transplanted kidneys was observed (Vats 2005;Moeller et al 2006). …”
Section: Genetics Of Sd-associated Glomerular Diseasementioning
confidence: 99%